Antibiotic susceptibility and molecular analysis of invasive Haemophilus influenzae in Canada, 2007 to 2014. (30th January 2017) - Tsang, Raymond S. W.; Shuel, Michelle; Whyte, Kathleen; Hoang, Linda; Tyrrell, Gregory; Horsman, Greg; Wylie, John; Jamieson, Frances; Lefebvre, Brigitte; Haldane, David; Gad, Rita R.; German, Gregory J.; et al.
Abstract : Background: Previously we studied the antibiotic susceptibility of invasive Haemophilus influenzae collected in Canada from 1990 to 2006 and characterized isolates by serotype, MLST and ftsI gene sequencing for significant PBP3 mutations. Objectives: To provide an update based on isolates collected from 2007 to 2014. Methods: A total of 882 case isolates were characterized by serotype using slide agglutination and PCR. MLST was carried out to determine ST. Isolates were tested for β-lactamase production, presence of significant PBP3 mutations and antibiotic susceptibility by disc diffusion against 14 antibiotics. MIC values of three antibiotics were determined for 316 isolates using microbroth dilution. Results: Non-typeable H. influenzae accounted for 54.6% of the isolates and 45.4% were serotypeable, predominantly type a (23.1%), type b (8.3%) and type f (10.8%). The overall rate of ampicillin resistance due to β-lactamase production was 16.4% and increased from 13.5% in 2007–10 to 19% in 2011–14. Significant PBP3 mutations were identified in 129 isolates (14.6%) with 23 (2.6%) also producing β-lactamase. MLST identified related STs (ST-136, ST-14 and ST-367) associated exclusively with genetically β-lactamase-negative, ampicillin-resistant isolates and confirmed previously reported associations between significant PBP3 mutations and ST. Conclusions: A significant increase in β-lactamase-producing isolates was observed from 2007 to 2014; the rate of significant PBP3 mutations has increased since previously reported and 52.5% of non-typeable H. influenzae now show resistance markers. Resistance to trimethoprim/sulfamethoxazole was common and no resistance to fluoroquinolones or third-generation cephalosporins was found.